The Brecht yearbook = Das Brecht-Jahrbuch. - Wessendorf, Markus (Camden House for the International Brecht Society, 2019)
Annual volume, this time featuring special sections on Brecht's dramatic fragments and on comedy in post-Brechtian theater, along with a variety of other contributions.